2002
DOI: 10.1007/bf03345087
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between the appearance of thyroid autoantibodies and development of destructive thyroiditis in patients undergoing treatment with two different type-1 interferons for HCV-related chronic hepatitis: A prospective study

Abstract: In this prospective study we performed repeated evaluations of thyroid status in patients undergoing treatment with different preparations of recombinant interferons (IFNs), in order to identify early markers of thyroid dysfunction. Moreover, we aimed to investigate whether the development of thyroid dysfunction was related to the appearance of thyroid autoimmunity. Our study included 51 consecutive patients without pre-existing thyroid disease, admitted to our hospital for Hepatitis C virus (HCV)-related chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…We observed similar trends between TD and euthyroid patients. Previous reports showed that the incidence of TAs in HCV-infected patients ranged from 10 to 45% (21,22,23). These observed differences might be related to geographical distribution, genetic variability, and environmental factors (24).…”
Section: Discussionmentioning
confidence: 93%
“…We observed similar trends between TD and euthyroid patients. Previous reports showed that the incidence of TAs in HCV-infected patients ranged from 10 to 45% (21,22,23). These observed differences might be related to geographical distribution, genetic variability, and environmental factors (24).…”
Section: Discussionmentioning
confidence: 93%
“…We can only speculate about the mechanism of action of IFN-a in this process and this is of interest as IFNmediated thyroid disease could constitute a model for human autoimmunity (13). With regard to the destructive phase of the disease, evidence has accumulated in favor of an autoimmune process, as it was demonstrated that production of thyroid autoantibodies preceded thyroid dysfunction (14) and, indeed, this phase looks like postpartum thyroiditis (15) and silent thyroiditis. Moreover, Graves' disease occurring after biphasic thyroiditis does not seem to be specific to IFN-a, as several case reports have described it after subacute thyroiditis (16), postpartum thyroiditis (17,18) or spontaneous thyroiditis (16) or even after treatment of euthyroid goiter by 131 I (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a subset of these patients may progress to permanent hypothyroidism, usually accompanied by the development of TAb's suggesting an underlying autoimmune thyroiditis. 16 Alternatively, the hypothyroidism may be due to a direct toxic effect of IFN␣ on the thyroid.…”
Section: Non-autoimmune Interferon Induced Thyroiditismentioning
confidence: 99%
“…1A) Previous studies have shown how IIT can cause serious complications of hyper-or hypo-thyroidism. 13,[16][17][18]37,39 Therefore, careful screening of all patients before, during, and after IFN␣ treatment is recommended. Since many symptoms of thyroid dysfunction could be attributed to HCV infection, clinicians should routinely look for signs of thyroid dysfunction such as tachycardia or bradycardia, sweating, heat or cold intolerance, unexpected weight loss or weight gain, and extreme fatigue and weakness.…”
Section: Direct Effects Of Ifn␣ On the Thyroidmentioning
confidence: 99%
See 1 more Smart Citation